Polish pronunciation animations developed on the basis of electromagnetic articulography - Lorenc, Anita (Lingua Posnaniensis, 2014)
This paper discusses the subject of pronunciation visualization, based on methodologies in experimental phonetics. It presents a brief survey of major Polish instrumental research into articulation, focusing primarily on contemporary dynamic visualizations using electromagnetic articulography. The author’s own investigations were conducted using an AG 500 articulograph, a device which records and visualizes the working and movement of the articulatory organs. Two speakers were recorded: one with standard pronunciation and the other with articulation defects. A multi-specialist team prepared vocal tract models, taking into account the speaker’s anatomical conditions as recorded with the articulograph, video recordings, and photographs. Articulographic data enabled the preparation of pronunciation animations of 45 words, which show the standard realization of all vowels and consonants of Polish, and eight animations of non-standard articulation.